2018
DOI: 10.1161/atvbaha.117.309846
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor

Abstract: Tissue factor (TF) is the high-affinity receptor and cofactor for factor (F)VII/VIIa. The TF-FVIIa complex is the primary initiator of blood coagulation and plays an essential role in hemostasis. TF is expressed on perivascular cells and epithelial cells at organ and body surfaces where it forms a hemostatic barrier. TF also provides additional hemostatic protection to vital organs, such as the brain, lung, and heart. Under pathological conditions, TF can trigger both arterial and venous thrombosis. For instan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
224
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(235 citation statements)
references
References 264 publications
0
224
0
11
Order By: Relevance
“…Further, previous studies showed that immunologic methods have different specificities and may include non-specific binding [ 31 , 32 ]. TF can be in an active or in an inactive state depending on its membrane phospholipid environment and status of a specific disulfide bond in the extracellular domain [ 33 , 34 ]. Immunoassays detect both active and inactive TF whereas EV-TF assays detect only active TF.…”
Section: Discussionmentioning
confidence: 99%
“…Further, previous studies showed that immunologic methods have different specificities and may include non-specific binding [ 31 , 32 ]. TF can be in an active or in an inactive state depending on its membrane phospholipid environment and status of a specific disulfide bond in the extracellular domain [ 33 , 34 ]. Immunoassays detect both active and inactive TF whereas EV-TF assays detect only active TF.…”
Section: Discussionmentioning
confidence: 99%
“…The major marker of the procoagulant state in CKD patients is the activation of the endothelial tissue factor. Tissue factor is a transmembrane protein and the main initiator of thrombin formation [88]. The upregulation of tissue factor is associated with cardiovascular disorders [89].…”
Section: Is Implication In Thromboinflammationmentioning
confidence: 99%
“…Circulating levels of factor VII were not altered during B. jararaca envenomation [25], and herein we showed that F7 mRNA levels are neither altered. However, we showed for the first time a decrease in hepatic F3 mRNA, which occurred as soon as 3 h after BjV administration, returning to control levels only at 24 h. TF expression is well known to differ depending on the tissue being analyzed, and to be regulated by several transcription factors, pathways and stimuli [75]. Interestingly, higher levels of constitutive TF expression seem to confer an additional hemostatic protection to specific tissues, such as lungs and heart.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 57%
“…Interestingly, higher levels of constitutive TF expression seem to confer an additional hemostatic protection to specific tissues, such as lungs and heart. However, under physiological conditions, TF levels in the liver are considered comparatively low in regard to other organs, and in low-TF transgenic mice (which have only ïżœ 1% of TF) the liver-specific hemostasis is considered normal, and those mice show no bleedings [75,76]. Further studies are currently being carried out to understand the importance of TF alterations during envenomation.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%